The Implementation of the Snakes and Ladders Game as a Learning Tool to improve Learning Outcomes in the Topic of Reaction Rates - Nadila Nadila; Jayadin Jayadin; Sri Astuti Rahman Coa (SEARCH: Science Education Research Journal, 2026)
Learning is a process of interaction between teachers, students, and their supporting elements, which are interrelated. However, in practice, students still have a low level of understanding of reaction rates, accompanied by suboptimal learning interest, resulting in less than optimal learning outcomes. One way to address this problem is to utilize engaging and interactive learning media, such as the chemical snakes and ladders game. This media is designed to help students understand the concept of reaction rates in a more enjoyable and meaningful way. This study aimed to determine the effect of using the chemical snakes and ladders game on student learning outcomes in reaction rates. The study was conducted at Waigete 1 State Senior High School using an experimental method with a one-group pretest-posttest design. Data collection was conducted through observation, interviews, and documentation, while data analysis was carried out using SPSS. Analysis techniques included a normality test, an N-Gain test, and a hypothesis test. The results showed a normally distributed data with a significance value of 0.096 for the pretest and 0.184 for the posttest. The N-Gain test obtained a percentage of 53 percent, which is categorized as moderate. Descriptive statistical tests showed that the data were centered around the mean value. The one sample test produced a significance value of 0.001 which is smaller than 0.05 so H1 is accepted.